2015
DOI: 10.1136/bcr-2014-206084
|View full text |Cite
|
Sign up to set email alerts
|

4D flow preliminary investigation of a direct carotid cavernous fistula due to a ruptured intracavernous aneurysm

Abstract: SUMMARYInadequate information is available about the cerebral blood flow and surgical strategies of a direct aneurysmal carotid cavernous fistula (daCCF). We report a quantitative analysis of flow velocity and volume using preoperative time-resolved phase-contrast MRI (fourdimensional (4D) flow MRI) in a daCCF. This is the first report of 4D flow findings with a daCCF. A 55-year-old woman developed a sudden headache and bruit of the right orbit, and MRI suggested the presence of a daCCF. Quantitative analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…We encountered a patient with PH due to isolated pulmonary artery involvement in large-vessel vasculitis, and evaluated the perioperative hemodynamic changes using 4D-flow MRI. Such perioperative assessments have been reported in cardiovascular and cerebrovascular diseases, and have demonstrated the importance of hemodynamic changes in surgical planning or therapeutic effects [1], [2], [3], [4], [5], [6], [7], [8], [9]. In patients with PH, Reiter et al demonstrated a relationship between mean PAP and vortical blood flow in the main pulmonary artery [1].…”
Section: Discussionmentioning
confidence: 96%
“…We encountered a patient with PH due to isolated pulmonary artery involvement in large-vessel vasculitis, and evaluated the perioperative hemodynamic changes using 4D-flow MRI. Such perioperative assessments have been reported in cardiovascular and cerebrovascular diseases, and have demonstrated the importance of hemodynamic changes in surgical planning or therapeutic effects [1], [2], [3], [4], [5], [6], [7], [8], [9]. In patients with PH, Reiter et al demonstrated a relationship between mean PAP and vortical blood flow in the main pulmonary artery [1].…”
Section: Discussionmentioning
confidence: 96%
“…The ICA occlusion rate with endovascular treatment is ranging from 17% to 47%. [ 20 ] Endovascular internal trapping is performed in cases with retrograde dome filling from collateral flow observed during BOT or if the aneurysm is extended to the bifurcation of the ophthalmic artery. In other cases, proximal ICA ligation is preferred.…”
Section: Discussionmentioning
confidence: 99%
“…A direct aneurysmal CCF was successfully treated by high-flow bypass using a RAG and ICA trapping in one case report. [ 20 ] Another study also found that high-flow bypass with aneurysm trapping is the appropriate surgical treatment to obliterate the fistula immediately in cases of CCA presented with direct CCF. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are also reported cases in the literature of ruptured cavernous carotid aneurysms as the cause of high-flow CCFs, [5][6][7] but many others have involved other pathology or iatrogenic trauma. One case series of spontaneous CCFs illustrated presentation with gradual onset EOM restriction, proptosis, or just injection of the conjunctiva that can occur in a variety of ages.…”
Section: Discussionmentioning
confidence: 99%